Gejala Serangan Lalat Buah (Bactrocera spp) dan Penerapan Pemasangan Perangkap Feromon yang Tepat dalam Mengendalikan Hama Lalat Buah pada Tanaman Terong (Solanum melongena L) - Fitriana, Meini; Kandila, Agustian; Nasution, Harlin; Ali Rusman, Muhammad; Wildan Al-ghifary, Muhammad; Lukito, Pendi; Arsi, Arsi (Seminar Nasional Lahan Suboptimal, 2021)
Fitriana M, Kandila A, Nasution H, Rusman MA, Al-Ghifary MW, Lukito P, Arsi A. 2021. Symptoms of  fruitfly (Batrocera spp) attack and application of correct installation of pheromone traps in controlling fruitflies on eggplant (Solanum melongena L). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 172-179.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Eggplant (Solanum melongena L.) is one of the plants with a wide distribution because it is include in the food ingredients of daily life. Fruitflies are small insects that are one of the pests on eggplant plants. The existence of this fruitfly was usually left alone by farmers because it could help pollinate eggplant (Solanum melongena L.). This observation aimed to determined the symptoms of fruit fly attacks and determine the proper installation of pheromone traps on eggplant plants (Solanum melongena L.). This research methodology was based on a literature study of scientific articles. Symptoms of attacks caused by fruitflies were in the form of puncture marks from the ovipositor. Fruitfly attacks were found on eggplants that were almost ripe so that the impact of these attacks on eggplants becomes rotten. The use of pheromones can reduced the use of insectisides. The proper installation of pheromone traps were placed the trap at distance of ±1.5 meters. The results of the pheromone trap obtained a ratio of 3:1 in the first bottle, 1:1 in the second bottle, and 1:1. This shows that there were more male fruit flies than female fruit flies. The conclusion of this observation shows that the symptoms of fruit fly attack such as the presence of puncture marks on almost ripe fruit, then the right strategy for applying pheromone traps with a distance of ±1.5 meters.